Rebels, scholars, explorers women in vertebrate paleontology - Berta, Annalisa (Johns Hopkins University Press, 2020)
"Not much has been written about the women who have helped define and develop the field of vertebrate paleontology over the last 100 years. The paleontologist coauthors of this book aim to remedy this situation by offering an international collection of compelling stories about the discovery, collection, and study of fossil vertebrates done by women paleontologists"--